Nuqūsh-i Bhūpāl / murattabah, Raz̤iyyah Ḥāmid, Rafʻat Sult̤ān. - Ḥāmid, Raz̤iyyah.; Sultān, Rafʻat. (Bābulʻilm Pablīkeshanz, 1996)
Contributed articles, chiefly on the history of Bhopal and contribution of Bhopal to Urdu literature.